Writing research questions and hypotheses: a genre-based investigation into writers' linguistic resources in social sciences - Lim, Jason Miin Hwa; Xianqing Luo (University of Belgrade, 2020)
Novice writers and university students often encounter problems with regard to (i) the extent to which they should include research questions and hypotheses in their research reports, and (ii) how they can effectively present these information elements to enhance clarity. To resolve these problems, we used a genre-based analytical framework and inputs provided by specialist informants to ascertain the prevalence of these information elements and the range of linguistic resources employed by writers in the research article introductions (RAIs) in two social sciences, namely Ethnic Studies (ES) and Industrial Relations (IR). We have found that most RAIs in IR incorporate research questions and hypotheses, while less than half of those in ES include them. The difference is attributable to writers’ greater tendency to employ epistemological methodologies in IR, and ontological methodologies in ES. Polar questions are rarely used in both disciplines, while factual, evaluative and circumstantial questions are far more prevalent. Active anticipatory verbs and that-clauses are used to postulate hypotheses in both disciplines, whereas first-person pronouns are far more common in ES than in IR. Our findings can be flexibly adapted to design instructional materials aimed at guiding novice writers in the formulation of research questions and hypotheses.